143 Caudate and Dorsolateral Prefrontal Cortex Beta Power Plays an Important Role in Working Memory Updating. (1st April 2022) - Qian, Helen; Williams, Ziv; Bick, Sarah K. B.
Abstract : INTRODUCTION: Working memory, the short-term maintenance and manipulation of information in memory, plays a crucial role in both daily functioning and complex cognitive tasks. Working memory impairment is a prominent feature of multiple neurocognitive disorders. Previous imaging work has demonstrated that caudate and dorsolateral prefrontal cortex (DLPFC) exhibit significant activity during working memory updating and maintenance, and previous animal work has suggested that caudate beta power plays an important role in updating information held in DLPFC. A better understanding of the neurophysiology underlying working memory is needed to develop novel treatment strategies such as neuromodulation. METHODS: Eight subjects who underwent depth electrode placement for medically refractory epilepsy participated in our study. Subjects participated in an auditory working memory task in which they heard a set of three syllables and then were prompted to repeat the syllables in either the original or reverse order. We computed beta power and coherence in caudate and DLPFC electrodes during working memory updating. RESULTS: Both caudate and DLPFC showed a peak in beta power during updating of working memory, and beta power was significantly higher for correct trials during this peak period compared to both incorrect and control trials. Just prior to beta power increase during working memory updating, there was also an increase in beta coherence between caudate and DLPFC. Coherence during this interval was significantly greater for correct trials as well. CONCLUSION: Caudate and DLPFC beta power and connectivity are important for updating information held in working memory.